OP0125 LIPID MEDIATOR PROFILES ASSOCIATE WITH PROGRESSION TO RA IN ANTI-CITRULLINATED PROTEIN ANTIBODY POSITIVE POPULATIONS - Vanderlinden, L.; Polinski, K.; Demoruelle, K.; Feser, M.; Seifert, J.; Mikuls, T.; Weisman, M.; Buckner, J.; Deane, K.; Clare-Salzler, M.; Robinson, W.; Holers, V. M.; et al. (Annals of the rheumatic diseases, 2023)
BackgroundLipid mediators are endogenously derived from the metabolism of omega-3 and omega-6 polyunsaturated fatty acids (PUFAs) and have important roles in promoting and resolving inflammation. PUFAs have been implicated in the pathogenesis of systemic inflammatory and autoimmune diseases, including rheumatoid arthritis (RA). Sharing many common pathways and key enzymes, individual lipid mediators may be correlated with one another and can be analyzed in combination as a profile. This study’s goal was to determine the association of PUFA-derived lipid mediator profiles with progression from RA-related autoimmunity, a state that can be identified in screened and studied individuals by the presence of peripheral blood anti-citrullinated peptide antibodies (ACPA) autoantibodies in the absence of arthritis, to clinically apparent RA.ObjectivesTo identify lipid mediator profiles in the preclinical period that are associated with progression to classifiable RA.MethodsUsing two unique prospective cohorts, the Targeting Immune Responses for Prevention of Rheumatoid Arthritis (TIP-RA) cohort and the Studies of the Etiologies of Rheumatoid Arthritis (SERA) cohort, we followed ACPA positive individuals in the absence of RA at baseline. We followed 81 and 79 participants in TIP-RA and SERA, of which 22 and 18 participants, respectively, developed RA during follow-up based on ACR/EULAR 2010 criteria (Table 1). Exposures included concentrations (pg/ml) of lipid mediators quantified from plasma samples via liquid chromatography tandem mass spectrometry, with profiles identified via principal component meta-analysis (metaPCA), which identifies common eigenspace between multiple datasets. Profiles were identified at two time periods: baseline (e.g. study enrollment) and pre-incident RA (just prior to RA in progressors or similar period in non-progressors). For each cohort, a Cox proportional hazard model was developed for each lipid mediator profile, adjusted for shared epitope status, age and smoking status. Meta-analysis was performed for each lipid mediator profile using Fisher’s method.ResultsAt each cross-section, the top 5 principal components (PC), selected based on scree-plots, were analyzed further. Analysis of the baseline cross-section identified a significant risk profile (baseline PC5, meta HR = 1.28, meta p-value = 0.033) and a suggestive protective profile (baseline PC1, meta HR 0.96, meta p-value = 0.055) associated with RA. The pre-incident RA period identified a significant risk profile (pre-incident RA PC4, meta HR = 1.37, meta p-value = 0.028). Figure 1 depicts the loading factors for the associated profiles. Both risk profiles (pre-incident RA PC4 and baseline PC5) had a mix of positive and negative loadings corresponding to important lipid mediators that are products of arachidonic acid (ARA) and eicosapentaenoic acid (EPA). These weights suggest higher levels of lipid mediators from EPA (an omega-3 FA) combined with lower levels of lipid mediators from ARA (an omega-6 FA) would be a risk factor for RA. The suggestive protective profile at baseline (baseline PC1) showed important lipid mediators with negative weights only, all high impact lipid mediators being descendants from linoleic acid (an omega-6 fatty acid), with lower levels being protective.ConclusionCombinations of lipid mediators show association with progression to RA, identifying multiple targets that could be potentially modulated to prevent the progression of disease.Table 1.Baseline Demographics of the ACPA+ Populations.TIP-RA Unaffected (n = 59)TIP-RA Progressed to RA (n = 22)SERA Unaffected (n=61)SERA Progressed to RA (n = 18)Female39 (61%)16 (73%)42 (69%)12 (67%)Non-Hispanic White49 (83%)15 (68%)53 (87%)15 (83%)Shared Epitope29 (49%)15 (68%)27 (44%)12 (67%)Age at baseline-year (SD)58.2 (12.6)55.8 (12.0)51.9 (13.8)50.6 (11.5)Ever smoked*18 (31%)8 (36%)27 (44%)8 (47%)First-degree relative with RA11 (19%)4 (18%)41 (67.2%)6 (33.3%)# of Study Visits2651893537112≥4010327*1 SERA subject missingREFERENCES:NIL.Acknowledgements:NIL.Disclosure of InterestsNone Declared.